KESULITAN BELAJAR PAI DI ERA NEW NORMAL PADA SISWA KELAS VIII SMP N 02 , KENAGARIAN BATAHAN, KECAMATAN RANAH BARATAHAN, KABUPATEN PASAMAN BARAT - Hermida; Junaidi; Salmi Wati; Arifmiboy (Universitas Pahlawan Tuanku Tambusai, 2022)
This research was motivated by events that occurred in the field that researchers saw in SMP 02 Ranah Batahan while studying PAI there were some who had difficulty understanding the material presented by the teacher during PAI learning in the new normal era. When the teacher gives long material, students have difficulty reading the material, besides that, students also have difficulty sending videos that are long. And besides that, students also have difficulty expressing opinions because the opinions issued by students are often immersed and unreadable by the teacher. This study uses a qualitative descriptive method, which describes the events that occur in the field as they are. Data collection that the author did by observation, and interviews. Research informants consist of key informants and supporting informants. Key informants were students of SMP 02 Ranah Batahan while supporting informants were teachers and parents. Data were analyzed by data collection techniques, data analysis techniques, and data triangulation. The results of this study regarding PAI learning difficulties in the new normal era in class VIII SMP 02 Ranah Batahan, Ranah Batahan District, namely students who do not have adequate communication tools, students have network difficulties, and students have limited quotas. So the solution that teachers do in overcoming learning difficulties in this new normal era is by creating interesting learning strategies, teachers convey learning materials creatively, reducing learning materials and teachers facilitating parents to ask the teacher directly what if students don’t understand. Keywords: Learning Difficulties, Islamic Religious Education, New Normal Era